The Influence of Weather Conditions and Available Soil Water on Vitis vinifera L. Albillo Mayor in Ribera del Duero DO (Spain) and Potential Changes Under Climate Change: A Preliminary Analysis - María Concepción Ramos (Agriculture)
Climate variability and trends are of increasing concern in grape-growing areas, although each cultivar can respond differently. In order to establish appropriate adaptation measures, it is necessary to know the relationship between climate variables and grape composition for each cultivar. This research attempts to provide information in this regard for the Albillo Mayor variety grown in the Ribera del Duero DO (Spain) and its potential changes under the shared socioeconomic pathways (SSPs) that lead to different radiative forcing targets. The response of this variety was evaluated in two plots during five seasons (2020–2024). For each year, the phenological dates and grape composition (berry weight, pH, titratable acidity, malic acid, alcoholic content, and the total polyphenol index) were evaluated and related to climate variables including maximum and minimum temperature and precipitation and the resulting water availability averaged over different periods within the growing season. Maximum and minimum temperatures in the pre-veraison period led to lower titratable acidity and malic acid, which, in addition, were favored by lower water availability in the same period. These conditions, on the contrary, led to an increase in the probable alcoholic degree, which is associated with a decrease in berry size. In addition, more available water during the ripening period increases the berry weight, which was also negatively affected by the difference between the maximum and minimum temperature in the same period. By 2050, with the predicted decrease in precipitation and increase in temperature, Albillo Mayor may undergo a decrease in acidity >14% and an increase in the probable alcoholic degree of about 5% in the SSP2-4.5 scenario (energy-balanced development, leading to a radiative forcing of 4.5 Wm−2), while changes could be up to 1.5 and 1.1 times greater, respectively, in the SSP5-8.5 scenario (heavily reliant in fossil-fueled development, leading to a radiative forcing of 8.5 Wm−2).